Project PRIME (Psychosocial Response to International Medical Electives): Results from Medical Trainees - Nicole E St Clair; Kristina Devi Singh-Verdeflor; Vanessa McFadden; Elizabeth Groothuis; Stephanie Lauden; Megan S McHenry; Stephen Merry; Stephen Warrick; Samantha L Wilson; James H Conway (Annals of Global Health)
Background: Participation in global health (GH) training experiences is common for US medical trainees (students, residents, and fellows). However, little is known about their experience of “culture shock” (CS), which frequently occurs during these transformative cross‑cultural immersions. Objectives: The objectives of this study include: (1) quantitatively measure medical trainee psychosocial responses to short‑term GH electives, (2) identify factors that influence their CS experiences, and (3) determine if the stage‑based CS conceptual framework applies to medical trainees. Methods: Undergraduate and graduate medical education trainees (UME and GME) who participated in short‑term GH electives between 2016 and 2020 were recruited across nine US institutions. Using a longitudinal survey method, we gathered data predeparture (demographics, resilience, perceived stress (PS), and CS assessments), every 5 days during the elective (CS, PS assessments, and training site conditions), and 30 days postreturn (perceptions of CS experiences). Analyses included summary statistics, linear regressions, and a linear mixed effects model (LMM). Findings: 252 trainees were enrolled, with 140 (56%) included in the LMM. The primary outcome was a culture shock profile (CSP) score, with 96% reporting CS. The only trainee‑specific factor that significantly increased CSP score was trainee type (UME > GME (+22%)). Several GH elective site‑specific factors significantly influenced CSP score (e.g., support network [−10%], role clarity [−11%], and overwhelmed by medical needs [+10%]). CS experiences were variable and did not progress in predictable, stage‑based fashions, which is discordant from common CS descriptions. Conclusions: Culture shock was a near‑universal, diverse experience during GH electives. On‑site training conditions and elective site host factors influenced CS more than trainee factors in this prepandemic cohort. Further research is required to (1) determine the optimal CS “balance” (i.e., promoting transformative learning while mitigating negative professional and personal impacts), (2) offer insight into harmful CS thresholds, (3) identify host perspectives, and (4) inform best practices for GH electives and global partnerships.